2009
DOI: 10.7861/clinmedicine.9-6-544
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing problems and dementia in acute hospital settings: practical guidance for the management of dysphagia

Abstract: -There is little evidence to support tube feeding in advanced dementia although it is still frequently used in acute hospital settings. Patients present with complex problems and are often unable to make decisions about their healthcare needs. Multidisciplinary teams may be challenged by the difficult ethical decisions they are required to make in the best interests of their patients. This paper guides decision making in the management of patients with dementia and dysphagia in the acute hospital setting. A st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…157,158,[160][161][162][163][164][165][166] The direction of discussions in this literature is that there remains much to do in clarifying the evidence base around decisions that need to be made -for instance extensive literature is available in relation to outcomes around PEG placement, 158,164 but how this is applied to specific populations or individuals (imminent vs nonimminent death; lacking capacity or not; different medical aetiologies; different co-morbidities present) awaits definitive answers. Decisions around nasogastric or PEG feeding and withdrawal of feeding support are particularly fraught areas.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…157,158,[160][161][162][163][164][165][166] The direction of discussions in this literature is that there remains much to do in clarifying the evidence base around decisions that need to be made -for instance extensive literature is available in relation to outcomes around PEG placement, 158,164 but how this is applied to specific populations or individuals (imminent vs nonimminent death; lacking capacity or not; different medical aetiologies; different co-morbidities present) awaits definitive answers. Decisions around nasogastric or PEG feeding and withdrawal of feeding support are particularly fraught areas.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Support for a focus on individual choices and quality of life was strongly indicated by the current study, which further identified the need for clinician self‐care and de‐briefing in this complex clinical area. In the dementia literature in particular, a growing body of work supports this view of feeding for comfort, which focuses primarily on the contribution of food and fluids to overall well‐being and quality of life, rather than nutritional needs . Similarly, as the population ages, there is a growing need for patient care in a palliative context.…”
Section: Discussionmentioning
confidence: 99%
“…Carroll and Zajicek described the experience in a 24-hour acute neurology unit in Plymouth. 3 They concluded that per 100,000 population, 10.8 hours of specialist registrar time and 11 hours of consultant time per week, 15 neurology beds and 90 outpatient appointments would be required. This study was performed before the European Working Time Directive came into force.…”
Section: John R Prowlementioning
confidence: 99%
“…1,2 There has been recent helpful guidance around oral feeding difficulties and ethical dilemmas. 3,4 …”
Section: Introductionmentioning
confidence: 99%